Generalized Statistical Convergence of order ? for Sequences of Fuzzy Numbers - Altinok, Hifsi; Karakas, Abdulkadir; Altin, Yavuz (Amer Inst Physics, 2018)
In the present paper, we introduce the concepts of Delta(m)-statistical convergence of order beta for sequences of fuzzy numbers and strongly Delta(m)-summable of order beta for sequences of fuzzy numbers by using a modulus function f and taking supremum on metric d for 0 < beta <= 1 and give some inclusion relations between them.
6th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 15-17, 2017 -- Budapest, HUNGARY
Keywords: Difference-Sequences; Geometric-Properties; Space; Delta